2022
DOI: 10.1108/ijm-07-2021-0398
|View full text |Cite
|
Sign up to set email alerts
|

University to work transition: a literature review

Abstract: PurposeThis article aims to describe the role universities should play in student to work transition.Design/methodology/approachAn objective bibliometric analysis is conducted and supported by qualitative assessments based on authors’ study of relevant papers.FindingsTwo themes emerge from the analysis: the first on the university's role in students' learning, skills and fits, in the transition process; the second on the university's role in engagement, motivation and support students in university-to-work tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Even after growing and exhaustive literature, there is no consensus about the potential determinants of smooth STWT. In their bibliometric study, Izzo et al (2022) provided a survey based on the periodic literature from 332 research articles. Numerous cited studies confirmed the significance of skill development and suggested that students' backgrounds (family and education) are determining factors for their entry into the labor market.…”
Section: School-to-work Transition and Its Determinantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even after growing and exhaustive literature, there is no consensus about the potential determinants of smooth STWT. In their bibliometric study, Izzo et al (2022) provided a survey based on the periodic literature from 332 research articles. Numerous cited studies confirmed the significance of skill development and suggested that students' backgrounds (family and education) are determining factors for their entry into the labor market.…”
Section: School-to-work Transition and Its Determinantsmentioning
confidence: 99%
“…Even after growing and exhaustive literature, there is no consensus about the potential determinants of smooth STWT. In their bibliometric study, Izzo et al . (2022) provided a survey based on the periodic literature from 332 research articles.…”
Section: School-to-work Transition and Its Determinantsmentioning
confidence: 99%
“…Gender disparities also play a critical role, with women typically experiencing slower transitions compared to men (Mills & Praeg, 2014;Nilsson, 2019). External circumstances such as family background, parental education, and area of residence signi cantly in uence UTWT (De Schepper et al, 2023;Izzo et al, 2022;Pastore & Zimmermann, 2019;Salas-Velasco, 2007). Evidence con rms that Mediterranean and Eastern European countries are characterized by signi cant degrees of unfair educational inequalities descending from family background (Liu et al, 2016;Palmisano et al, 2022;Salas-Velasco, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the STWT model incorporates factors that impact the transition from secondary school to the workplace (Masdonati et al, 2022). The university-to-work transition represents another critical juncture and a challenge for the higher education system that is expected to prepare students for future careers in a rapidly changing and stressful world of work (Izzo et al, 2022). In this context, research highlights meaningful work as a primary objective for university students and emphasizes the need for career counseling services to guide them in attaining meaningful future careers (Allan et al, 2017).…”
Section: Introductionmentioning
confidence: 99%